Human Resource Management in Efforts to Improve the Quality of Education at SMA Ma'arif Kadungora, Garut - Mulyana, Deni (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Human resource management in educational institutions must be carried out continuously because it aims to improve the quality of education in these educational institutions. However, there are still many educational institutions that do not pay attention to the management of human resources, so that these educational institutions lack quality. This study aims to analyze how planning, recruitment and selection, training and development, as well as compensation of human resources in an effort to improve the quality of education at SMA MA'ARIF Kadungora – Garut. This research uses a qualitative approach with a case study type. Research subjects were determined by purposive sampling technique which includes school principals, teachers, and administrative staff. Data collection techniques are: observation, in-depth interviews, and documentation. Data analysis uses the interactive model from Miles, Huberman and Saldana. The validity of the data is tested by source triangulation, technique triangulation, and membercheck. The results showed: (1) Planning for the placement of homeroom teachers is held routinely at the beginning of each new school year, while planning for the selection of vice principals and principals is held every three years; (2) Recruitment and selection are announced publicly by forming a special committee and there are several requirements that must be met; (3) Training and development comes from various parties such as the Ministry of Religion, Ministry of Education, Culture, Research and Technology, MGMP, KKM, Training Centers, Universities, and from SMA MA'ARIF itself; (4) Compensation is given in the form of honoraria, leave, and recreation. The compensation system for basic salary is equalized with differences in the amount of benefits received.